Endolysosomal Mesoporous Silica Nanoparticle Trafficking along Microtubular Highways - Achraf Noureddine; Michael L. Paffett; Stefan Franco; Alfonso E. Chan; Sandeep Pallikkuth; Keith Lidke; Rita E. Serda (MDPI AG, 2021)
This study examines intra- and intercellular trafficking of mesoporous silica nanoparticles along microtubular highways, with an emphasis on intercellular bridges connecting interphase and telophase cells. The study of nanoparticle trafficking within and between cells during all phases of the cell cycle is relevant to payload destination and dilution, and impacts delivery of therapeutic or diagnostic agents. Super-resolution stochastic optical reconstruction and sub-airy unit image acquisition, the latter combined with Huygens deconvolution microscopy, enable single nanoparticle and microtubule resolution. Combined structural and functional data provide enhanced details on biological processes, with an example of mitotic inheritance during cancer cell trivision.